Crimes of writing : problems in the containment of representation (Oxford University Press, 1991)
From the origins of modern copyright in early eighteenth-century culture to the efforts to represent nature and death in postmodern fiction, this pioneering book explores a series of problems regarding the containment of representation. Stewart focuses on specific cases of "crimes of writing"--The forgeries of George Psalmanazar, the production of "fakelore," the "ballad scandals" of the eighteenth and nineteenth centuries, the imposture of Thomas Chatterton, and contemporary legislation regarding graffiti and pornography. In this way, she emphasizes the issues wh